Policy Against Drop-out in Italy - Colombo, Maddalena (Central European Journal of Educational Research, 2019)
In this essay I set out the current situation of Early School Leaving (ESL) in Italy by considering both data provided by institutional sources (national and international) and a review of the most recent contributions from the educational work that have been done intensively to fight against ESL over the last 20 years. I will argue that the way followed so far will not lead to surprising results, due to deep and structural persisting factors of inequality. After a short overview on the position of Italy in the European rankings, the article recalls the main interventions that took place in the country by different investors (public and non-public), setting up a multiplicity of fragmented macro-politics. Then I will look at the mechanisms of differentiation and unequal distribution of educational opportunities and I will conclude with suggestions on how to make the fight against ESL more efficient and forward-looking.